Turkish Nationalism and the Incorporation of Migrants and Minorities into the Turkish State: a Study in the Civic and Ethnic Contours of Turkish Nationalism - Conrad-Bradshaw, Jared (Border Crossing, 2018)
This article uses the integration of immigrants and minorities into Turkey as a lever to investigate the boundaries of Turkish nationalism. Turkish nationalism is often treated as an ethnic nationalism, and that’s indeed how it was thought of by many of its Ottoman founders. However, the legal system is constructed in a largely civic way, such that ethnic heritage—in theory—does not matter for citizenship. Immigrants and domestic minorities provide a useful lens to look at who is included within the category of “Turk”. This article uses the integration of immigrants and minorities into Turkey as a lever to investigate the boundaries of Turkish nationalism. Turkish nationalism is often treated as an ethnic nationalism, and that’s indeed how it was thought of by many of its Ottoman founders. However, the legal system is constructed in a largely civic way, such that ethnic heritage—in theory—does not matter for citizenship. Immigrants and domestic minorities provide a useful lens to look at who is included within the category of “Turk”.